2009
DOI: 10.1111/j.1533-2500.2008.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Histological Changes after the Administration of a Continuous Intrathecal Clonidine in Wistar rats

Abstract: These findings showed that continuous intrathecal administration of clonidine did not produce evidence of histological neurotoxicity; therefore it is possible that continuous administration of intrathecal clonidine might be a safe option for treatment of chronic intractable pain; however, further investigations are necessary for evaluating diverse doses and periods of time, and to define its possible behavioral effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…Clonidine mimics the effects of norepinephrine and it antihyperalgesic mechanisms that partly depend on fortification of noradrenergic inhibitory controls in the dorsal horn of the spinal cord [10]. The safety of intrathecal clonidine has been extensively evaluated in animals, humans, and obstetrical anesthesia [6, 1116]. Also it is reported that clonidine administrated via intrathecal route was undetectable in the fetal circulation with no obvious effect on the neonatal Apgar scores [12, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Clonidine mimics the effects of norepinephrine and it antihyperalgesic mechanisms that partly depend on fortification of noradrenergic inhibitory controls in the dorsal horn of the spinal cord [10]. The safety of intrathecal clonidine has been extensively evaluated in animals, humans, and obstetrical anesthesia [6, 1116]. Also it is reported that clonidine administrated via intrathecal route was undetectable in the fetal circulation with no obvious effect on the neonatal Apgar scores [12, 16].…”
Section: Introductionmentioning
confidence: 99%
“…No evidence of spinal pathology was observed. Similarly, intrathecal administration for 14 days did not result in toxicity in the adult rat (29,30). These findings are based on histological evaluation performed by a neuropathologist, and similar methodology here has also failed to demonstrate histopathology in the cord of neonatal and young rats following single dose intrathecal clonidine.…”
Section: Discussionmentioning
confidence: 86%
“…In adult animals, repeated injections or continuous infusions of spinally administered clonidine for 14 days or longer, have not produced neurotoxic effects in rats (29,30) or dogs (31,32), and bolus doses did not reduce spinal cord blood flow in sheep (33) or pigs (34). …”
Section: Introductionmentioning
confidence: 99%
“…This method allows for repeated intrathecal injection into the CSF via a catheter. The disadvantage of this technique is the need for chronic intrathecal catheterisation that causes non-specific histological changes, but intrathecal injections are technically difficult in rats and repeated injections are therefore not feasible [33]. One previous study evaluated the impact of a single intrathecal HES injection in a pig model.…”
Section: Discussionmentioning
confidence: 99%